Opportunities for digitalization of export and import processes in Uzbekistan - Toshtemirova Muxlisa Davronbek kizi (THE INNOVATION ECONOMY, 2026)
This article explores the relevance, current state, and prospects of digitalizing export and import processes in the Republic of Uzbekistan. The analysis shows that the wide implementation of digital technologies in foreign trade can enhance transparency, reduce bureaucratic barriers, and increase competitiveness in international markets. The paper examines existing challenges and proposes practical solutions, including the creation of a unified digital platform, the transition to electronic document circulation, the use of artificial intelligence, and the improvement of digital literacy among entrepreneurs.